Trapped in Self-Sabotage Patterns: The Role of Coping Styles in Early Adulthood with Emotionally Immature Parents - Al-aida, Alfia Najwa; Islam, Azizah Fajar (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2024)
This study aims to examine the role of coping style in early adulthood with emotionally immature parents on the level of self-sabotage. The background of this research is based on the phenomenon observed in individuals who grow up with emotionally immature parents, often facing difficulties in problem-solving and engaging in self-sabotaging behaviors. This study uses a quantitative method with simple linear regression analysis to test the relationship between coping style and self-sabotage. The results show a significant relationship between the two variables, with an internalizing coping style showing a negative correlation and an externalizing coping style showing a positive correlation with self-sabotage. The effect of coping style on Self-sabotage is recorded at twenty-one percent, with the internalizing coping style having a greater impact than the externalizing coping style. This study concludes that coping style plays an important role in shaping Self-sabotage behaviors in early adulthood with emotionally immature parents. It is hoped that this research will serve as a reference for future studies and provide further insights into the relationship between coping style and Self-sabotage in individuals with emotionally immature family backgrounds.